Fundamentals mechanism of legal regulation - Сарновська, C. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2007)
The issue of the definition and content of the regulation mechanism is one of the center-lnyh seats in the science of the general theory of law. The mechanism of regulation should be seen not as set of separate legal means, but as a dynamic system of interacting legal phenomena. START blyve place in the legal regulation belongs to the general legal permits and general yurydychnimzaboronam. General legal permits and general legal prohibition are also important legal hulyatoramy re-directing legal origins in different areas of public relations.